2022
DOI: 10.1186/s13046-022-02376-4
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 mediated inflammasome activation promotes oral squamous cell carcinoma progression via JAK2/STAT3/Sox4/NLRP3 signaling pathway

Abstract: Background Interleukin-6 (IL-6) has been reported to be critical in oral squamous cell carcinoma (OSCC). However, the set of pathways that IL-6 might activate in OSCC are not fully understood. Methods IL-6 and Sox4 expressions were first determined with RT-qPCR, ELISA, Western blot, or immunohistochemistry in OSCC tissues, and correlations between IL-6 and Sox4 expression and patient pathological characteristics were examined, and Kaplan–Meier appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 65 publications
2
25
0
Order By: Relevance
“…We analyzed the protein-coding potential of candidate circRNAs to confirm the possibility of protein translation ( Figure 6 A). The protein-coding potential of seven circRNAs was confirmed using two prediction tools: CPC 2.0 and CPAT [ 38 , 39 ]. It was confirmed that some circRNAs, except circSnx12 and circUsp3, are highly likely to code proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed the protein-coding potential of candidate circRNAs to confirm the possibility of protein translation ( Figure 6 A). The protein-coding potential of seven circRNAs was confirmed using two prediction tools: CPC 2.0 and CPAT [ 38 , 39 ]. It was confirmed that some circRNAs, except circSnx12 and circUsp3, are highly likely to code proteins.…”
Section: Resultsmentioning
confidence: 99%
“…We used the coding potential calculator 2 (CPC 2.0, accessed on 25 January 2023) and the coding potential assessment tool (CPAT, accessed on 25 January 2023) for the prediction of coding potential for the selected circRNAs [ 38 , 39 ]. To predict circRNA-interacting proteins, we performed the analysis as previously described [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the Nod-like receptor protein 3 (NLRP3) inflammasome can be primed or indirectly activated by inflammatory cytokines (e.g. IL-1β, IL-6) that are often found as components of the SASP (38,(54)(55)(56).…”
Section: Nlrp3 Caspase-1 and Gasdermin D Mediated Pyroptosis Underlie...mentioning
confidence: 99%
“…Such a rise in MMP levels accelerates and enlarges the degradation of interstitial and peritumoral matrices, creating new space for the proliferation and invasion of cancer cells and thereby augmenting the size of the tumor mass ( Figure 2 ). It should also be considered that the inflammatory cytokines and growth factors whose synthesis is promoted by CD147 can directly promote OSCC proliferation [ 140 , 199 , 200 , 201 ]. Moreover, the survival and growth of OSCC cells are sustained by the activation of AKT and MAPK, which follows CD147 triggering ( Figure 1 and Figure 2 ) [ 61 , 62 , 63 , 64 , 65 ].…”
Section: Cd147 and The Growth Of Osccmentioning
confidence: 99%